Characteristics and vitreoretinal management of retinal detachment in eyes with Boston keratoprosthesis. Issue 5 (26th August 2016) - Petrou, Petros; Banerjee, Philip J; Wilkins, Mark R; Singh, Mandeep; Eastlake, Karen; Limb, G Astrid; Charteris, David G
Abstract : Purpose: To review the incidence and features of vitreoretinal complications of a permanent Boston keratoprosthesis and to report the use and outcomes of 23-gauge vitrectomy to manage vitreoretinal pathology. Design: Retrospective non-comparative, interventional case series. Subject, Participants: 27 eyes of 27 patients managed with a Boston keratoprosthesis at Moorfields Eye Hospital over a 3-year period. Methods: All eyes that underwent pars plana vitrectomy (PPV) and had at least 6 months follow-up were analysed with a specific focus on the anatomical and histological characteristics of retinal detachment and outcomes of surgery. Main outcome measures: Anatomical success and characteristics of retinal detachment over the follow-up period. Results: 27 patients underwent Boston keratoprosthesis implantation over the study period. Of these, six (22%) required PPV for retinal detachment which demonstrated a specific pattern of serous elevation with subsequent severe anterior proliferative vitreoretinopathy (PVR). The mean follow-up period was 9 months (range 6–14 months). At final follow-up, visual acuity ranged from perception of light to 6/18, and five of six cases had attached retinae under the silicone oil. Histological analysis of a subretinal membrane demonstrated a predominantly glial/retinal pigment epithelium fibrocellular tissue, consistent with PVR. Conclusions: The study showed that retinal detachment complicated by PVR, as demonstrated by the clinical and histological characteristics of this condition, is common in patients undergoing Boston keratoprosthesis. We also showed that 23-gauge vitrectomy can be effectively performed in patients with a permanent prosthesis. Visual acuity often remains poor, despite successful anatomical results.